The theoretical and empirical analysis of trade integration among unequal partners : implications for the Southern African Development Community - Cattaneo, Nicolette Sylvie (Rhodes University, Faculty of Commerce, Department of Economics, 1998)
The re-acceptance of South Africa into the international community has cleared the path for the closer integration of South Africa with its neighbours in a broader southern African regional union. In particular, the countries of the Southern African Development Community {SADC), which South Africa joined in August 1994, have committed themselves to the formation of a free trade area (FTA) over an eight-year period. The most likely impediment to this process is the perception of a highly unequal distribution of the economic gains and losses of such an arrangement. This reflects the particular context of SADC: one of a comparatively undeveloped region, dominated by a relatively large, more industrially advanced country, which is itself small by international standards. The essential question with which this study is concerned, therefore, is whether, despite the existing inequalities in the region, a FTA among SADC members could be mutually beneficial to South Africa and its partners. The thesis applies orthodox and new trade theory to the analysis of economic integration among unequal partners. Using the theoretical analysis, and with reference to empirical studies of such experience elsewhere in the world, it attempts to provide an assessment of the existing body of literature on the possible effects of a SADC FTA. In the light of this discussion, and from its own preliminary empirical analysis of the possible pattern of inter-sectoral versus intra-sectoral specialisation which may result on union, the study suggests ways in which a fuller evaluation of the welfare implications of a southern African FTA may be achieved. The thesis argues that the orthodox theory based on perfect competition provides an insufficient framework for the analysis of the likely effects of a SADC FT A. It finds that, firstly, in an alternative analytical framework which retains the assumption of perfect competition, there may be other criteria for judging the success of a regional union that are neglected by orthodoxy, particularly in the case of developing countries. Secondly, the new trade theory based on imperfect competition and product differentiation provides useful insights into the possible effects of a regional union among countries at unequal levels of development. The formal extension of this body of literature to the theory of economic integration is clearly called for. It is found, however, that neither orthodox customs union theory, nor its suggested alternatives and extensions, enable one to conclude, a priori, that the formation of a FTA in the southern African region could not be beneficial to both South Africa and its smaller partners. Further, the present empirical studies on SADC do not take account of the full range of factors necessary for a complete welfare assessment of the possible effects. Since the outcome of integration depends on the empirical circumstances of the particular case, and since the information necessary for a comprehensive welfare evaluation is not currently available, the study concludes that the countries of the region have committed themselves to a FTA without any definite knowledge of its likely effects.
Keywords: Southern African Development Community; Customs unions; Africa, Southern -- Foreign economic relations; Africa, Southern -- Economic integration